STRATEGI GEREJA DALAM MEMBANGUN PELAYANAN KONTEKSTUAL BAGI GENERASI Z DI ERA DIGITAL - Nani, Naomi; Sirait, Hikman; Rahayu, Esti (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
Generation Z is a unique generation. They are born and grew up in a rapid advancing technological era, especially digital technology. Yet, churches often ignore their uniqueness so that the services they hold are not aligned to Generation Z style. Therefore, Churches need to provide special strategies to embrace and reach them through contextual services. Starting from this case, the research aims to find strategies in holding a contextual services for generation Z in the digital era. This research is qualitative descriptive with a literature study method.The result of the research show three important strategies that must be considered to develop contextual services, firstly a partnership-based service strategy, secondly a needs-based service strategy, and thirdly a technology-based service strategy.